Ten‐Year Secular Trends in Youth Violence: Results From the Philadelphia Youth Risk Behavior Survey 2003‐2013. (April 2017) - Pool, Andrew C.; Patterson, Freda; Luna, Ingrid Y.; Hohl, Bernadette; Bauer, Katherine W.
ABSTRACT: BACKGROUND: Youth violence reduction is a public health priority, yet few studies have examined secular trends in violence among urban youth, who may be particularly vulnerable to numerous forms of violence. This study examines 10‐year secular trends in the prevalence of violence‐related behaviors among Philadelphia high school students. METHODS: Repeated cross‐sectional data were analyzed from 5 waves of the Philadelphia Youth Risk Behavior Survey (YRBS) from 2003 to 2013. Sex‐specific multivariate regression models were used to examine secular trends in multiple types of violence, accounting for age, race/ethnicity, and sampling strategy. RESULTS: In 2013, the most prevalent violent behavior was physical fighting among boys (38.4%) and girls (32.7%). Among girls, the prevalence of sexual assault and suicide attempts declined between 2003 and 2013 (β = −0.13, p = .04 and β = −0.14, p = .007, respectively). Among boys, significant declines in carrying a weapon (β = −0.31, p < .001), carrying a gun (β = −0.16, p = .01), and physical fighting (β = −0.35, p = .001) were observed. CONCLUSIONS: Whereas the prevalence of some forms of violence stabilized or declined among Philadelphia youth during 2003‐2013 time span, involvement in violence‐related behaviors remains common among this population. Continued surveillance and evidence‐based violence reduction strategies are needed to address violence among urban youth.